FORMATION OF AN ADAPTIVE MODEL OF THE CONTAINER TERMINAL FUNCTIONING TECHNOLOGY - Prodashchuk , S. M.; Baulina , H. S.; Bohomazova , H. Ye.; Chekhunov, D. M. (Systems and Technologies, 2026)
Container terminals play a crucial role in organizing rail container transportation, as they contribute to the rapid and safe handling of cargo, while also optimizing logistics processes. However, in today’s environment, the existing technology for handling containers at terminals does not ensure uninterrupted operation, which worsens the quality of transportation services and does not meet all the needs of transportation stakeholders. Due to the downtime of containers and loading and unloading equipment, railways and other participants in the transportation process suffer losses. Therefore, instead of stationary cranes, the use of reach stackers is proposed in the work, and the relevance of their application is justified. The article formalizes the technology of container terminal operation in the form of a stochastic adaptive model. The criterion for the optimality of the objective function is the minimum operating costs when processing containers. The model takes into account the risk of possible financial losses associated with the failure of loading and unloading machines during container processing. Risk events are considered, which are proposed to include organizational and technical delays and force majeure circumstances in the operation of reach stackers. The risk of financial losses is represented by a polynomial distribution law and a second-order Erlang distribution density function. The proposed model of the container terminal operation technology adapts the existing technology to the unstable conditions of its operation, which allows to ensure safe working conditions and reduce the risks of railway transport workers. The study takes into account the risks of potential losses associated with the failure of loading and unloading machines during container handling. The proposed adaptive model can be used in the future when designing new container terminals, as well as for modernizing and restoring existing ones